PENGGUNAAN E-LEARNING UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR BIOLOGI MATERI SISTEM SARAF SISWA KELAS XI IPA 2 SMA XYZ - Eva Zahora; Saparso (Journal of Innovation Research and Knowledge, 2021)
This action research was aimed to find out the use of e-learning to improve students’ interests and biology learning outcome on the nervous system material of grade XI Science 2 “XYZ” Senior High School which consists of 40 students. This research was conducted in two cycles and each cycle had four steps which were planning, implementation, observation and reflection/evaluation. The data were analyzed using qualitative descriptive analysis techniques. The data was collected from test material, questionnaires, open-ended essays, teacher and IT staff’s observation notes, pre tests and post tests. The result of this research showed that there were improvements of students’ interests towards the learning process. The percentage result in the early observation was 75.55%, in Cycle I was 87.5%, and in Cycle II was 93%. It showed that the students had interests in the learning process. Furthermore, the improvements also occurred to the students’ learning outcomes. In the early observation, there were only 15.25% students who passed the passing grade. Subsequently, in Cycle I and II, the students who passed the passing grade were 90% and 95%. In conclusion the use of e-learning could improve students’ interests and biology learning outcome on the nervous system material of Grade XI Science 2 “XYZ” Senior High School.